Effects of natural between-days variation in sleep on elite athletes` psychomotor vigilance and sport-specific measures of performance - Knufinke, M.; Nieuwenhuys, A.; Maase, K.; Moen, M. H.; Geurts, S. A. E.; Coenen, A. M. L.; Kompier, M. A. J. (Journal of Sports Science & Medicine, 2018)
Performance capacity in athletes depends on the ability to recover from past exercise. While evidence suggests that athletic performance decreases following (partial) sleep deprivation and increases following sleep extension, it is unclear to which extent natural variation in sleep impacts performance. Sleep quantity and, for the first time, sleep stages were assessed among 98 elite athletes on three non-consecutive nights within a 7-day monitoring period, along with performance tests that were taken on standardized times each following morning. Performance assessment included psychomotor performance (10-minute psychomotor vigilance task) and sport-specific tests of fine (e.g., accuracy) and gross motor skills (e.g., endurance, power). Mixed-effects models were employed to assess the effect of sleep quantity (total sleep time (TST), sleep onset latency (SOL), wake after sleep onset, sleep efficiency) and sleep stage duration (light, deep, REM) on performance. Average TST was 7:30 ± 1:05 hours, with a mean variation of 57 minutes across days. Longer TSTs were associated with faster reaction times (p = 0.04). Analyses indicated small and inconsistent effects of sleep quantity (TST, SOL) and sleep staging (light sleep) on gross motor performance, and no effects on fine motor skill performance.